Distribution network reconfiguration based on incorporation data platform and improved PSO - Chen, Shu-Heng; Dang, Xiao-Qiang; Li, Xing-Yuan; Liu, Qun-Ying (Dianli Xitong Baohu yu Kongzhi, 2012)
An improved distribution network reconfiguration algorithm is presented by embedding niche operation into discrete PSO based on incorporate database platform. Firstly, the evaluating model of fitness value comprehensively considering line loss, voltage loss, load balance and breaker acting cost is presented; then, the discrete PSO is improved by embedding niche operation process; further, the distribution reconfiguration system is developed based on distribution SCADA database platform. Lastly, two distribution systems are studied. The results prove that the improved discrete PSO is reliable while the calculating process is speeded.